Inhibiting Nigerian cultural heritage crimes through penal laws (2014)
From time immemorial, crimes against cultural heritage have always been frowned at and anyone who decides to sell these ‘sacred objects’ will be jeered at. Only the so called ‘outcasts’ in the family or community dared to dabble into the illegal sale of cultural objects. Over the years, trade in cultural objects has become lucrative. Attempts have been made in the Nigerian laws to ensure that items of our cultural heritage do not leave the shores of the country illegally by penalizing certain behaviors in relation to cultural objects. This article takes a cursory look at the impact of heritage crimes nationally and globally and considers if the legislation in Nigeria has been able to adequately put the situation under control thereby achieving the aims of sentencing.